De la pestilence à la fragrance. L’origine de l’ambre gris selon les auteurs arabes - Thierry Buquet (OpenEdition, 2016)
The origin of ambergris, an intestinal pathologic secretion of the sperm-whale, used in perfumes and medieval pharmacology, had been long debated among Arab scholars. The paper exposes the various hypotheses related to this origin, and its textual transmission during medieval times. These traditions show a good example of complex relations between good and bad odors, connected to the different colors of ambergris (black, grey, white) and to its animal (whale or fish-dung), mineral or vegetal origin.